God : the failed hypothesis : how science shows that God does not exist - Stenger, Victor J., 1935-2014; Hitchens, Christopher, 1949-2011 (Amherst (N.Y.) : Prometheus books, 2008)
De boodschap is duidelijk: God bestaat niet.
Keywords: Atheism; God -- Proof; Religion and science